2014
DOI: 10.1353/jhr.2014.0035
|View full text |Cite
|
Sign up to set email alerts
|

Saving Lives: Evidence from a Conditional Food Supplementation Program

Abstract: Many governments in developing countries implement programs that aim to address nutrional failures in early childhood, yet credible evidence on the effectiveness of these interventions is scant. This paper evaluates the impact of a large-scale, government-run, food forti cation program-the Programa de Alimentación y Nutrición Nacional (PANN) 2000-on child mortality in Ecuador. The program was implemented by regular administrative staff at local public health posts and consisted of offering a free micronutrient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…26 of these (16 RCTs and 10 CBAs) were used in meta-analyses. With the exception of Meller 40 , all included studies were found in published data. Twenty-six studies had some data that could be included in meta-analyses.…”
Section: Results Of Literature Search and Description Of Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…26 of these (16 RCTs and 10 CBAs) were used in meta-analyses. With the exception of Meller 40 , all included studies were found in published data. Twenty-six studies had some data that could be included in meta-analyses.…”
Section: Results Of Literature Search and Description Of Studiesmentioning
confidence: 99%
“…Using a regression discontinuity design, Meller and his colleagues 40 found a significant reduction in child mortality (from 2.5% to 1% or 1.5%) during the eight months of exposure to Ecuador's PANN program of supplementary feeding and health care checks. This represents a 40 to 60% decrease in mortality.…”
Section: Mortalitymentioning
confidence: 99%
“…Having compared the consequences of imposing economic sanctions and the Millennium Development Goals and the Sustainable Development Goals, one can view sanctions as a counterbalance to the mechanism of sustainable development (Table 6). (Shah, 2017, Meller and Litschig, 2014, Akbulut-Yuksel, 2014, Guthmuller, Jusot, and Wittwer, 2014 3 Providing a healthy lifestyle and promoting well-being for all at any age The threat to the well-being of the population (the sanctions imposed on Iraq and Haiti were implemented without violent intervention) (Kokoshin, 2005) 10 Reducing inequalities within and between countries…”
Section: Achievability Of Sustainable Development Goals In Condition mentioning
confidence: 99%
“…Four studies involved giving psychosocial stimulation (for example, weekly play sessions with a community health aide), [35][36][37][38] four programmes provided other health interventions (such as a community-wide sanitation programme or visits from health workers) and two of these also provided maternal education. 28,39,40 Two programmes provided nutritional education.…”
Section: Implementation Of Supplementary Feeding Programmesmentioning
confidence: 99%
“…Looking at deaths, Meller and colleagues 39 found that a supplementary feeding programme in Ecuador reduced the rate of deaths from 2.5% to 1-1.5%; a 40-60% decrease in the number of deaths. This promising result, however, was not observed in a study in Niger, where there was no difference in deaths between children who received supplementary food and those who did not.…”
Section: Illness and Deathmentioning
confidence: 99%